Resilience in occupational therapy students. - de Witt, Patricia Ann; Monareng, Luther; Abraham, Aaishah AH; Koor, Safiyya; Saber, Rizwana (South African Journal of Occupational Therapy, 2019)
At the University of the Witwatersrand, occupational therapy undergraduate students perceived their programme to be more stressful than similar health science education programmes, resulting in students experiencing mental health issues. Thus, the purpose of this study was to determine the level of resilience and stress and health behaviours of students registered in the undergraduate Occupational Therapy programme. A descriptive quantitative cross-sectional on-line survey design was used, replicating an American study of nursing students by Ahern. Permission was obtained from Ahern to use the same battery of data collection tools: demographic questionnaire, the resiliency scale; the perceived stress visual analogue scale and the health behaviours questionnaire. Once ethical clearance was obtained, the data collection battery plus an information sheet was mailed electronically to 205 students. The three questionnaires were scored as prescribed and all other data were analysed descriptively. The Kruskal-Wallis ANOVA was used to test the significant difference between the variables and Spearman's rank order correlation coefficient to determine associations between the questionnaires as well as the subtests. One hundred and seventeen questionnaires were analysed. Results indicated high stress levels within this cohort, with the major stressor being academic. Most students reported a medium level of resilience and the health behaviour questionnaire revealed a low risk. There was no significant difference between the different years and the only variables found to have a significant association was stress over the year increasing risk-taking behaviours. It was concluded that all students could benefit from some resilience training. Those who lived away from home and had poor social support were the most vulnerable.